Hakikat dan Konsep-Konsep Dasar Psikologi Pendidikan, Belajar dan Pembelajaran Serta Faktor-Faktor yang Mempengaruhinya - Rusdi Rusdi (Politeknik Negeri Padang, 2014)
Is a must for every educator who is responsible, that he was in carrying out his duties,act in a manner consistent with the \